Abscisic Acid (ABA) Regulation of Arabidopsis SR Protein Gene Expression - Cruz, Tiago (2014)
Serine/arginine-rich (SR) proteins are major modulators of alternative splicing, a key generator of proteomic diversity and flexible means of regulating gene expression likely to be crucial in plant environmental responses. Indeed, mounting evidence implicates splicing factors in signal transduction of the abscisic acid (ABA) phytohormone, which plays pivotal roles in the response to various abiotic stresses. Using real-time RT-qPCR, we analyzed total steady-state transcript levels of the 18 SR and two SR-like genes from Arabidopsis thaliana in seedlings treated with ABA and in genetic backgrounds with altered expression of the ABA-biosynthesis ABA2 and the ABA-signaling ABI1 and ABI4 genes. We also searched for ABA-responsive cis elements in the upstream regions of the 20 genes. We found that members of the plant-specific SC35-Like (SCL) Arabidopsis SR protein subfamily are distinctively responsive to exogenous ABA, while the expression of seven SR and SR-related genes is affected by alterations in key components of the ABA pathway. Finally, despite pervasiveness of established ABA-responsive promoter elements in Arabidopsis SR and SR-like genes, their expression is likely governed by additional, yet unidentified cis-acting elements. Overall, this study pinpoints SR34, SR34b, SCL30a, SCL28, SCL33, RS40, SR45 and SR45a as promising candidates for involvement in ABA-mediated stress responses.